2012
DOI: 10.1021/es300474z
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Records of Polycyclic Aromatic Hydrocarbons (PAHs) in the Continental Shelf of China: Implications for Evolving Anthropogenic Impacts

Abstract: Sources, compositions, and historical records of polycyclic aromatic hydrocarbons (PAHs) in sediment cores collected from the Yellow Sea and the South China Sea were analyzed to investigate the influence of anthropogenic activities. The occurrence of PAHs was mainly derived from various combustion sources, especially the combustion of biomass and domestic coal. Uniform composition of sedimentary PAHs (52−62% of phenanthrene, benzo[b]fluoranthene, indeno[1,2,3-cd]pyrene, and benzo[g,h,i]perylene) suggested air-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(59 citation statements)
references
References 48 publications
7
51
1
Order By: Relevance
“…In the present study, the mean values of these two indices both decreased from 2005 (0.37 and 0.53) (Huang et al, 2009) to 2010 (0.29 and 0.46), uniformly suggesting similar , and those of straw decreased 69% (68%). Our recent findings that the levels of sediment PAHs became steady or even lower in the PRD and adjacent coastal region may have been reflective of a shift in energy consumption patterns in South China, e.g., natural gas, liquefied petroleum gas and other environmentally friendly energy types have been increasingly used during the last few years Liu et al, 2012a).…”
Section: Occurrence and Spatial Distribution Of Particulate Matter Tmentioning
confidence: 97%
“…In the present study, the mean values of these two indices both decreased from 2005 (0.37 and 0.53) (Huang et al, 2009) to 2010 (0.29 and 0.46), uniformly suggesting similar , and those of straw decreased 69% (68%). Our recent findings that the levels of sediment PAHs became steady or even lower in the PRD and adjacent coastal region may have been reflective of a shift in energy consumption patterns in South China, e.g., natural gas, liquefied petroleum gas and other environmentally friendly energy types have been increasingly used during the last few years Liu et al, 2012a).…”
Section: Occurrence and Spatial Distribution Of Particulate Matter Tmentioning
confidence: 97%
“…They mainly originate from anthropogenic activities, such as incomplete combustion of organic materials (e.g., wood, coal oil, gas, tobacco and straw), as well as from automobile exhausts and industrial processes (Yunker et al, 2002a(Yunker et al, , 2002b. As a result, PAHs have been used to assess the magnitude of anthropogenic impacts on the environment (Jones et al, 1989;Page et al, 1999;Liu et al, 2012bLiu et al, , 2012cYang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the outcome may be debatable, recent studies have observed declining trends of sediment contamination by polycyclic aromatic hydrocarbons [2,3], a group of organic pollutants partially derived from anthropogenic sources, which are consistent with an increase in the amount of cleaner energy (natural gas and liquefied petroleum) consumed and a decrease in the use of coal, a more traditional energy type [3].…”
mentioning
confidence: 88%